PENGEMBANGAN ASEAN WE FEELING DI SMA DIPONEGORO TUMPANG KABUPATEN MALANG - Rijal, Najamuddin Khairur; Kurniawati, Dyah Estu; Suhermanto, Dedik Fitra (Jurnal BALIRESO, 2018)
ASEAN Community has been officially implemented since early 2016. Although there is a longtime between the idea of ASEAN Community agreed and accepted in 2003 and its implementationin 2015, the understanding of society about ASEAN Community still low. Even though, ASEANCommunity is ready to integrate Southeast Asian society through political-security, economic, andsocio-cultural dimensions. Therefore, it takes a lot of efforts to develop awareness and ASEAN wefeeling, one of them through community service program. This paper describes activities ofcommunity service program to develop ASEAN we feeling in Senior High School DiponegoroTumpang in Malang Regency, East Java. These activities include socialization of ASEANCommunity and ASEAN socio-cultural, decor classes competition with ASEAN-themed, ASEANCorner initiation, and development of ASEAN-oriented schools. These activities are to increasestudents knowledge about ASEAN and ASEAN Community and developed ASEAN we feeling asan ASEAN society.